2021
DOI: 10.1039/d1gc02306c
|View full text |Cite
|
Sign up to set email alerts
|

The life-cycle environmental performance of producing formate via electrochemical reduction of CO2 in ionic liquid

Abstract: Carbon capture and utilisation provide a means to mitigate climate change caused by anthropogenic greenhouse gas emissions by delaying carbon emissions via temporary storage in goods. This article presents a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Life cycle assessment (LCA) is a widely accepted ISO-standardized methodology for quantifying the environmental profiles of products in a holistic way. The LCA is a powerful tool that allows identification of trade-offs to support decision- and policy-making implementation, which has been used for assessing electrochemical reduction of CO 2 . ,, Chatzisymeon and co-authors compared the environmental impacts of laboratory-scale treatment of olive mill wastewater using EO, wet air oxidation, and photocatalytic oxidation, and they concluded that the EO was more environmentally friendly . On the other hand, however, the laboratory-scale processes are often far from being optimized in terms of resource efficiency and economic benefits .…”
Section: Introductionmentioning
confidence: 99%
“…Life cycle assessment (LCA) is a widely accepted ISO-standardized methodology for quantifying the environmental profiles of products in a holistic way. The LCA is a powerful tool that allows identification of trade-offs to support decision- and policy-making implementation, which has been used for assessing electrochemical reduction of CO 2 . ,, Chatzisymeon and co-authors compared the environmental impacts of laboratory-scale treatment of olive mill wastewater using EO, wet air oxidation, and photocatalytic oxidation, and they concluded that the EO was more environmentally friendly . On the other hand, however, the laboratory-scale processes are often far from being optimized in terms of resource efficiency and economic benefits .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of data on industrial-scale production of ILs, a set of simple methods and assumptions have been carried out to calculate the life cycle inventory (LCI) . The “cradle to gate” or “cradle to grave” life cycle assessment (LCA) approaches have been used to analyze the environmental impacts of IL catalysts or separation processes such as acetylsalicylic acid synthesis using 1-butyl-3-methylimidazolium bromide, natural gas dehydration using 1-ethyl-3-methylimidazolium bis­(trifluoromethylsulfonyl)­imide, fluorinated gas recovery using 1-ethyl-3-methylimidazolium perfluoropentanoate, carbon capture and storage using 1-butyl-3-methylimidazolium bis­(trifluoromethylsulfonyl)­imide ([BMIM]­[NTf 2 ]), formate synthesis using trihexyltetradecylphosphonium 1,2,4-triazolide, cellulosic biofuel production using cholinium lysinate, and cellulose dissolution with 1-butyl-3-methylimidazolium chloride ([BMIM]­[Cl]) . Their common findings were that ILs usually perform worse than their corresponding reference substances in almost all environmental impact categories .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical CO 2 reduction reaction (CO 2 RR) to valueadded products using renewable energy has been considered as an economically attractive approach for reducing the amount of CO 2 in the atmosphere. [1][2][3][4] Among the possible CO 2 electroreduction products, formate as an important chemical intermediate and hydrogen carrier, is one of the most economical and viable products of the CO 2 RR. [5][6][7][8][9] Over the past decades, vigorous efforts have been made to develop electroreduction systems for high-efficiency CO 2 RR to formate.…”
Section: Introductionmentioning
confidence: 99%